A Network Pharmacology of Beluntas (Pluchea indica) on Immunity Cases - Fauzi, M Amir; Muchlisin, M Artabah; Jamil, Ahmad Shobrun; Almuhtarihan, Irsan Fahmi (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2023)
COVID-19 is classified as an outbreak related to the human immune system. The process of spreading was indeed quick, which made this outbreak a particularly dangerous pandemic. As of March 10, 2023, Indonesia had recorded 6,738,225 positive cases and 160,941 deaths from COVID-19 in 2020. The aim is to curb virus spread by boosting the immune system through antibody production. Studies suggest that certain Indonesian plants have immunomodulatory potential. This study aimed to determine the protein network associated with the body's immune system, which was activated by giving beluntas ( Pluchea Indica ). The research method used is descriptive in silico analysis using a online databases: KNApSAck, Dr. Duke, Pubchem, Swiss ADME, Swiss Target Prediction, Gene Cards, Venny, STRING, and KEGG. Based on the results of pharmacological network analysis, the P. indica contains 234 secondary metabolites, 126 of which have high bioavailability. Proteins associated with P. indica contain 1317 compounds, and those related to immunomodulators contain 1380 proteins. 340 proteins were found to have interacted with P. indica, all linked to immunomodulation, suggesting its potential for developing treatments for immune-related disorders through further research Based on KEGG Pathway analysis, there are five critical pathways in the immunomodulatory system, namely Th17 cell differentiation, IL-17 signaling pathway, T cell receptor signaling pathway, Fc epsilon RI signaling pathway, and TNF signaling pathway. There is 17 compound that can be an immunomodulator because it interacts with five critical pathways in the immunomodulator system.